Analytical Study of Shariah Guidelines for Different Classes in the Light of the Quran and Sunnah - Nasib Ullah (Journal of Religion and Society, 2026)
It is an analytical paper and a case study on Shariah rules about various classes of people in the perspective of Quran and sunna and how Islam is a holistic balanced system to regulate the life of individual and community. The necessity to refer to divine guidance towards different sectors of the society has become more pressing in a world where change has been a constant factor and where moral relativism and a decline in social institutions are the order of the day. The paper contends that Islamic doctrine is not limited to rituals and self-piety but being prolific to family life, social relationships, economic behavior, forms of Government and education and concerns the individual liability and right of various classes of the society. Based on the Quran and the original Sunnah as the main sources, the given research will analyze the Shariah prescriptions in regards to individuals, family, social and economic groups, rulers and state apparatus and the academic and educational community. In an effort to highlight this unity and practical applicability, the study assumes a qualitative and analytical approach, and considers the general principles that are agreed upon as opposed to juristic disputes. It goes to show that even though Islam appreciates the variance in roles, capacities, and social status, it equally maintains universal values of justice, responsibility, compassion and moral responsibility. The paper also discusses how Shariah principles strive to create a balance on rights and obligations, guard against exploitation and injustices and to ensure the social harmony. Through its response to the modern issues- economic inequality, family breakdown, abuse of power and degradation of ethics, the paper demonstrates that the Quran and Prophetic teachings are also topical and can offer long-term solutions to the existing problems. The results confirm that Islam presents a living and comprehensive system of orientation that is capable of adjusting to the evolving situations without undermining the fundamental moral and spiritual values. Finally, the article also finds that the submission of Shariah-based advice to the various social classes is the only way to reform morality, achieve social stability, and deliver justice within the Muslim societies. Keywords: Shariah Guidelines; Qur’an and Sunnah; Social Classes in Islam; Islamic Social Ethics; Rights and Responsibilities; Contemporary Challenges